Potential impact of the joint association of total bilirubin and gamma-glutamyltransferase with metabolic syndrome - Makoto Shiraishi; Muhei Tanaka; Hiroshi Okada; Yoshitaka Hashimoto; Shinichi Nakagawa; Muneaki Kumagai; Teruyuki Yamamoto; Hiromi Nishimura; Yohei Oda; Michiaki Fukui (Diabetology & Metabolic Syndrome, 2019)
Abstract Background Metabolic syndrome is characterized by the clustering of different metabolic abnormalities. Total bilirubin and gamma-glutamyltransferase (GGT) levels have been reported to be associated with this condition. However, the extent to which the interaction between these parameters affects metabolic syndrome is unknown. Therefore, we examined the association of total bilirubin and GGT levels with metabolic syndrome, and investigated the combined effect of the two parameters. Methods In this retrospective cohort study, we analyzed 8992 middle-aged Japanese subjects (4586 men, 4406 women; mean age, 44.8 ± 9.3 years) without metabolic syndrome from a cohort of employees undergoing annual health examinations. They were divided into four groups according to median total bilirubin and GGT levels: both-low, GGT-high, total bilirubin-high, and both-high. The incident of metabolic syndrome was evaluated during a follow-up of 2.8 ± 1.2 years. Results The incident rate of metabolic syndrome during the follow-up was 4.6% in the both-low group, 12.1% in the GGT-high group, 2.7% in the total bilirubin-high group, and 10.6% in the both-high group. Total bilirubin and GGT have an interaction effect on the risk of incident metabolic syndrome (p = 0.0222). The both-low [hazard ratio (HR), 1.37; 95% confidence interval (CI) 1.002–1.89], GGT-high (HR, 1.88; 95% CI 1.42–2.52), and both-high (HR, 2.07; 95% CI 1.56–2.80) groups showed an increased adjusted HR for incident metabolic syndrome after adjusting for covariates compared with the total bilirubin-high group. Conclusions The simultaneous presence of high total bilirubin and low GGT levels may be associated with a lower incidence of metabolic syndrome.